An Investigation of Different Determinants of Default Risks: Evidence from Chinese Commercial Banks - SHI, YINGQI (2019)
Default risk was likely one of the most significant factors in the 2008 global financial crisis, which caused major adverse impacts on global financial markets. Banks were significantly affected during the crisis and play a pivotal role in the functioning of the global economy. Therefore, it is hugely important to investigate why banks default as doing so will help mitigate future crises and maintain the stable growth of the banking sector. Until now, however, far too little attention has been paid to the default risks facing commercial banks in China and it is not clear whether CAMELS variables will affect banks’ decisions to default. The purpose of this investigation is to explore the determinants of default risk for commercial banks in China. Based on this purpose, this study examines 226 commercial banks in China between 2013-2018 using Pooled OLS, fixed-effects model, random-effects model, and generalized method of the moments. In addition, the growth rate of NPLs is employed as a proxy to reflect the default risk of commercial banks. According to a quantitative analysis of CAMELS indicators, ownership, and financing differences, the results of this research show that asset quality of commercial banks is the most significant factor in default risk, and that, in the future, listed banks are less likely to face credit risk than unlisted banks.